KULIA KERJA LAPANGAN TEMATIK MENDUKUNG MBKM MAHASISWA INDO GLOBAL MANDIRI MENDAPING PARA TUNAWISMA BERTAHAN HIDUP PADA PERKUMPULAN SIKH DI AUSTRALIA BARAT - Irena, Angelina; Hertati, Lesi; Hendarmin, Rum; Asmawati; Romri, Arsi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
This study aims to find information on the factors that cause homelessness in Western Australia and efforts to overcome these factors by using the interview method. In this study, researchers conducted interviews with 20 homeless people with managers/organizers, instructors, and inmates. This interview aims to obtain research information, namely about the guidance applied, the methods used, the motivating and inhibiting factors, as well as efforts to overcome the obstacles followed by the provision of food on Moore Street which was obtained from the soup kitchen or bakery. The findings in this study, in the life of the homeless, it can be seen that the occurrence of homeless people and beggars can be divided into two causal factors, namely internal factors and external factors. Internal factors include lazy, unwilling to work, not mentally strong, physical or psychological disabilities. While external factors include social, cultural, economic, educational, environmental, religious and geographical factors.